Rural training pathways: the return rate of doctors to work in the same region as their basic medical training - Matthew R. McGrail; Belinda G. O'Sullivan; Deborah J. Russell (BMC, 2018)
Abstract Background Limited evidence exists about the extent to which doctors are returning to rural region(s) where they had previously trained. This study aims to investigate the rate at which medical students who have trained for 12 months or more in a rural region return to practice in that same region in their early medical career. A secondary aim is to investigate whether there is an independent or additional association with the effect of longer duration of rural exposure in a region (18-24 months) and for those completing both schooling and training in the same rural region. Methods The outcome was rural region of work, based on postcode of work location in 2017 for graduates spanning 1-9 years post-graduation, for one large medical program in Victoria, Australia. Region of rural training, combined with region of secondary schooling and duration of rural training, was explored for its association with region of practice. A multinomial logistic regression model, accounting for other covariates, measured the strength of association with practising in the same rural region as where they had trained. Results Overall, 357/2451 (15%) graduates were working rurally, with 90/357 (25%) working in the same rural region as where they did rural training. Similarly, 41/170 (24%) were working in the same region as where they completed schooling. Longer duration (18-24 vs 12 months) of rural training (relative risk ratio, RRR, 3.37, 1.89-5.98) and completing both schooling and training in the same rural region (RRR: 4.47, 2.14-9.36) were associated with returning to practice in the same rural region after training. Conclusions Medical graduates practising rurally in their early career (1-9 years post-graduation) are likely to have previous connections to the region, through either their basic medical training, their secondary schooling, or both. Social accountability of medical schools and rural medical workforce outcomes could be improved by policies that enable preferential selection and training of prospective medical students from rural regions that need more doctors, and further enhanced by longer duration of within-region training.